Delayed bleeding after prophylactic bilateral internal iliac artery balloon occlusion in elective caesarean hysterectomy for the management of placenta accreta - Othman, Abdul Karim; Razak, Noraslawati; Mat, Mohd Hanif Che (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Morbidly adherent placenta (MAP) can be divided into placenta accrete, placenta increta and placenta percreta. It is associated with high parity, multifetal gestation, advanced maternal age, assisted reproductive technologies, placenta previa, and more importantly a history of caesarean section or uterine surgery. Globally, the incidence of placenta accrete has increased and seems to be in parallel with the increasing rate of caesarean section delivery. Despite rapidly evolving diagnostic imaging, and growing of surgical expertise, morbidly adherent placenta (MAP) remains an important cause of maternal morbidity and mortality, especially related with life-threatening postpartum haemorrhage. Although the choice of treatment for placenta accrete is puerperal hysterectomy, this procedure itself involves a greater risk of intra-operative haemorrhage. Elective caesarean hysterectomy using prophylactic bilateral internal iliac artery balloon occlusion offer an interesting approach which can minimize the risk of intra-operative haemorrhage. However, our case report describes the case of a 28-year old Gravida 3 Para 2 morbidly obese parturient diagnosed to have placenta previa type 3 posterior with accrete who experienced a complication of life threatening massive bleeding post-operatively after an elective caesarean hysterectomy using a prophylactic bilateral internal iliac artery balloon occlusion intra-operatively.